ANALISIS T TEST PERBANDINGAN KOMPUTER SERVER LINUX DEBIAN 9 DAN WINDOWS SERVER 19 DENGAN VMWARE - Wahyun, Maulia; Zulfa, Ira; Amna, Amna (Jurnal Teknik Informatika dan Elektro, 2023)
The Laboratory of the Faculty of Engineering, Gajah Putih University is the place to be observed in conducting research on the T Test comparison analysis of Debian 9 and Windows Server 19 Linux server computers with VMware. Analysis is an investigation of a study to make a comparison or ratio, namely the difference or difference between two or more values, where comparisons are often used to convey the advantages or disadvantages of something that you want to research such as doing research on a Debian 9 Linux server computer with Windows Server 19 using T Test as a test in statistical measurement of the proposed hypothesis to compare the average between the two populations, where the T Test results show the Sig table, namely 0.005 < 0.05 and t count 3.643 > t table 1.782. So, the results obtained are that there is an influence, namely the Nil Hypothesis (H0) is rejected and the Alternative Hypothesis (Ha) is accepted.